2008
DOI: 10.1111/j.1365-2133.2008.08731.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of an epidermal stem cell marker, cytokeratin 19, in cutaneous squamous cell carcinoma

Abstract: These results suggest that CK19 expression may be associated with the retention of stem cell characteristics or a state that is uncommitted to terminal squamous differentiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 14 publications
3
42
1
Order By: Relevance
“…Aberrant expression of CK19 has been reported in oral SCC, and, more recently, in cutaneous SCC. [14][15][16] Chen et al showed that cutaneous SCCs, compared with actinic keratosis and squamous cell carcinoma in situ, expressed CK19 to a greater extent (80%) and this expression correlated with the Ki-67 labelling index. 16 According to the authors, this CK19 overexpression in SCCs reflects the immaturity of the tumour cell lineage as it may disrupt terminal differentiation and preserve stem cell characteristics and the ability of the cells to multiply.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Aberrant expression of CK19 has been reported in oral SCC, and, more recently, in cutaneous SCC. [14][15][16] Chen et al showed that cutaneous SCCs, compared with actinic keratosis and squamous cell carcinoma in situ, expressed CK19 to a greater extent (80%) and this expression correlated with the Ki-67 labelling index. 16 According to the authors, this CK19 overexpression in SCCs reflects the immaturity of the tumour cell lineage as it may disrupt terminal differentiation and preserve stem cell characteristics and the ability of the cells to multiply.…”
Section: Discussionmentioning
confidence: 95%
“…4,[27][28][29] Although few studies have examined the expression of CK15 and CK19 in basal cell carcinoma (BCC) and SCC, only rarely have nestin expression been examined in the two most common cutaneous malignancies. 5,16,[30][31][32] Furthermore, expression of stem cell markers, to the best of our knowledge, has not been examined in Merkel cell carcinoma (MCC), which is well known for its expression of both epithelial and neural markers. In this study, we immunohistochemically examined the expression of stem cell markers CK15, CK19 and nestin in BCC, SCC and MCC.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…A variety of markers have been reported in the diagnosis of porocarcinoma; however, there is overlapping staining pattern seen in SCC (Table 1) [4,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Both porocarcinoma [4,11,12] and SCC [10,11,25] can express EMA.…”
Section: Introductionmentioning
confidence: 94%
“…73 Significantly higher CK19 expression has recently been demonstrated in squamous cell carcinoma compared with actinic keratosis or Bowen disease. 74 Nestin and CD133 show significantly higher expression in melanomas compared with benign naevi, and in metastatic compared with primary melanomas. 77 Thus, progression from benign to malignant to metastatic disease appears to be mediated by pathways that restore the stem cell features and characteristics.…”
Section: Prognostic Implicationsmentioning
confidence: 97%